The effect of systemic injury score on the decision making of mangled lower extremities. Issue 10 (October 2016) - Yeh, Hsuan-keng; Fang, Frank; Lin, Yu-Te; Lin, Cheng-Hung; Lin, Chih-Hung; Hsu, Chung-Chen
Abstract: Purpose: Mangled lower extremity with Mangled extremity severity score (MESS) more than 7 are considered unsalvageable. We are looking for a factor helps us predicting the salvage potential in the patient with MESS score between 7 and 9. Materials and methods: We reviewed the patients with lower extremities open fracture type IIIB or IIIC and received salvaged procedure or amputation in CGMH between 2002/01 and 2010/09. The patients are subgroup according to their MESS score. ISS score, Gustilo open fracture classification were compared between patient with successful salvage and patient with delay amputation. Logistic regression and stepwise modeling were used to determine the effect of each covariate. Results: 242 patients were enrolled in the study. 33 patients had primary amputation, 160 patients had successfully salvaged limbs and 49 patients received delay amputation. Among patients with MESS score less than 7, 116 patients had successful salvage limbs and 7 patients received delay amputation. Among patient with MESS between 7 and 9, 44 patients discharged with salvaged limbs and 39 patients were failed to salvage their limbs. Successful salvaged patients in this group had significant lower ISS score in compare to delay amputated patients. Patients with ISS score more than 18 in this group has higher delay amputated rate (P value = 0.01). Conclusion: Systemic injury severity score can help us tell potentially salvaged patient from potentially amputated patient. In patients with MESS score between 7 and 9 concurrently have ISS score less then 17 are potentially salvageable. Level of Evidence & Study Type: Level 3 Retrospective cohort study/prognostic study